Preparation and Characterization of Polyethylenimine Functionalized Reduced Graphene Oxide for Thermoelectric Applications. (27th August 2021) - Nanthini, S.; Shalini, M.; Sathiyamoorthy, Suhasini; R., Kumar; Ikeda, Hiroya; H., Shankar; Maaza, Malik; Veluswamy, Pandiyarasan
Abstract : A facile and rapid hydrothermal route is used to synthesize the reduced graphene oxide (rGO) using polyethyleneimine (PEI) as a reducing agent. Structural and morphological studies confirm the degree of reduction, which is also verified by Raman analysis. Synthesized rGO has a nanosheet-like structure with wrinkles and folded regions. Hall measurements were taken at room temperature and measured its carrier concentration, resistivity, and mobility. Raman spectrum confirms that there is a change in shift while introducing a polymer. Thermoelectric characterizations were taken and found a decrease of oxygen content in rGO compared to GO. The values of Carrier concentration, resistivity and mobility are determined by Hall measurements at room temperature were rGO (p-type) is 3.95 × 10 19 (cm 3 ), 2.71 × 10 −3 (ohm-cm), 58.3 (cm 2 V −1 s −1 ) where for (n-type) rGO is 1.53 × 10 20 (cm −3 ), 2.57 × 10 −3 (ohm-cm), 15.9 (cm 2 V −1 s −1 ) respectively. The carrier concentration of P-type rGO is higher when compared to n-type rGO. We believe that prepared reduced graphene oxide (rGO) will be used for wearable thermoelectric applications.